Pre-donation interview as a tool to maintain the safety of donated blood: Assessment from bioethics - Birnenbaum, Silvia Judith (Southern perspective / Perspectiva austral, 2024)
Donor selection is essential. The pre-donation questionnaire includes updated information on risk behaviors or exposures that could be associated with transfusion-transmissible diseases. This document serves to identify the initial period of an infection or the presence of diseases not analyzed in the laboratory. The donor is the first link in the transfusion safety chain. Considering their word as an irreplaceable tool, it is worth asking what is the value of their testimony to avoid transfusing contaminated blood.We sought to analyze, from the perspective of bioethics, the value that donor testimony entails for the safety of the blood components to be transfused. Interviews were formalized with members of the health team to assess their assessment of the donors' contribution to transfusion safety. From the analysis of the data, the weakness of the pre-donation questionnaire is evident. The fragility of the process clearly lies in the selection of candidates. It is verified that the donor's testimony cannot be replaced by another tool in the qualification. This contributes to transfusion safety proportionally to the truthfulness provided by the donor. From the perspective of the health team, the donor's testimony is scarcely appreciated, due to its lack of veracity. In particular, difficulty in interpreting the questions on the selection form is evident, due to the lack of donation education among the applicants.